Analysis and Optimization of Incompressible Inviscid Flow around Split Flap Airfoils - Mohamed Ahmed, Osman (1997)

(untitled)
Generally airfoils are designed for cruise flight conditions; but during take-off and landing, when the airplane flies at low speeds and small angles of attacks, the lift provided by single airfoils is not sufficient, and an extra lift is required for safe landing and take-off. In this condition the use of high lift devices is important. When an airfoil is accompanied by high lift devices the system is referred to as multi-component airfoil configuration. When high lift devices are deflected, the geometry of the airfoil is changed temporarily. As a result the effective chamber, angle of attack, and area of the airfoil are increased; consequently, the lift is increased too, since the lift is directly proportional to the chamber, the angle of attack, and the airfoil area. The advantage of this is that the landing and take-off speeds are reduced, a fact that gives the pilot more time to react, in case any accident happens during take-off or landing. At the same time, the runway length is also reduced. If the airplane is fast and it's carrying capacity is high, then the importance of using multi-component airfoils increases, because the value of the lift increment necessary for safe take-off and landing is high. At the present time, the importance of multi-component airfoils is increasing due to the high competition between airplane manufacturing companies, whose aim is to produce new models of airplanes with higher speeds and carrying capacities than the airplanes used today. Future airplanes should be fast, safe, and large. Achievement of these requirements in future airplanes is strongly related to the use of the appropriate multi-component airfoil designs. And this is why much experimental and computational work needs to be devoted to analyze and optimize the flow around multi-component airfoil configurations. When dealing with multi-component airfoil configurations computational methods are of great importance so as to focus the zone of the optimal flap position for the maximum lift coefficient. Then the experimental work is to be carried out within that zone. This saves long expensive wind tunnel, and flight test hours. In the investigation presented in this thesis, a computer program, which models incompressible inviscid flow around an airfoil with a split flap, has been developed. The program is based on the pioneering Hess and Smith panel method. The new program is referred to as MULTFOIL.